(untitled) (American Journal of Islam and Society, 1997)
The workshop on the Islamization of knowledge, organized by the Kulliyyah of Islamic Revealed Knowledge and Human Sciences, was held at Regency Hotel, Port Dickson, Negeri Sembilan, Malaysia, from June 7-11, 1996. Workshops and seminars of this sort usually revolve around the nature, characteristics, and rationale for the Islamization of knowledge. This workshop, however, was different in that it dealt with the question of methodology. Given that Islamization is an intellectual and methodological outlook, the workshop’s emphasis on methodology is justified and well placed. Clearly, the workshop was not for the uninitiated or for new recruits. It was meant for those who have been associated with the movement for the Islamization of knowledge and especially for those who have the potential to make some contribution toward its realization. Clearly, the list of participants indicates that the organizers selected those who are imbued with a spirit of selflessness and zeal to work for the sake of Islam to uplift the Ummah’s image intellectually and otherwise.The workshop, as briefed by Louay Safi, was an occasion to scrutinize in minute detail the parameters of the Islamization of knowledge, to critically appreciate the contributions made by the leading luminaries, and to grapple seriously with questions of methodology ...